METAPHORICAL MODEL OF THE IMAGE OF A WOMAN IN A POETIC TEXT (ON THE EXAMPLE OF ENGLISH AND UZBEK LANGUAGES) - Jo'raqulova Mohiro'y; Aliqulova Dildora (Western European Studies, 2025)
The article analyzes the metaphorical model of the female image in English and Uzbek poetry based on cognitive and linguopoetic approaches. Metaphors representing the image of a woman are distinguished, and their conceptual content, semantic features, and cultural interpretation are determined. The results show that in English poetry, the image of a woman is associated with spiritual experiences and individuality, and in Uzbek poetry - with kindness, purity, and national values. The study comparatively illuminates the universality and national identity of the concept of femininity.
Keywords: female image; metaphor; linguopoetics